2014
DOI: 10.1021/ef5020428
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation: The Behavior of Asphaltene in Crude Oil and at the Oil/Water Interface

Abstract: Carboxyl asphaltene is commonly discussed in the petroleum industry. In most conditions, electroneutral carboxyl asphaltene molecules can be deprotonated to become carboxylate asphaltenes. Both in crude oil and at the oil/water interface, the characteristics of anionic carboxylate asphaltenes are different than those of the carboxyl asphaltenes. In this paper, molecular dynamics (MD) simulations are utilized to study the structural features of different asphaltene molecules, namely, C5 Pe and anionic C5 Pe, at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
106
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(111 citation statements)
references
References 48 publications
5
106
0
Order By: Relevance
“…The sharp peaks observed at $0.4 nm indicated the parallel stacking of asphaltenes due to pp interactions in the aromatic regions which agreed with previous experimental and simulation data (Pisula et al, 2005;Jian et al, 2014). The small peaks located at 0.75 and 1.1 nm suggested the T-shape stacking as demonstrated by Gao et al (2014). Moreover, the intensity of interactions between LHA and asphaltenes was independent on the type of asphaltenes in context of this study, because the number of asphaltene-LHA intermolecular contacts differed very slightly between ASP1 and ASP2 (Fig.…”
Section: Aggregation At the Toluene-water Interfacesupporting
confidence: 89%
See 1 more Smart Citation
“…The sharp peaks observed at $0.4 nm indicated the parallel stacking of asphaltenes due to pp interactions in the aromatic regions which agreed with previous experimental and simulation data (Pisula et al, 2005;Jian et al, 2014). The small peaks located at 0.75 and 1.1 nm suggested the T-shape stacking as demonstrated by Gao et al (2014). Moreover, the intensity of interactions between LHA and asphaltenes was independent on the type of asphaltenes in context of this study, because the number of asphaltene-LHA intermolecular contacts differed very slightly between ASP1 and ASP2 (Fig.…”
Section: Aggregation At the Toluene-water Interfacesupporting
confidence: 89%
“…3). The interface is identified as the region where the water density is 10-90% of the value in its bulk phase (Frost and Dai, 2011;Gao et al, 2014), which is highlighted as dotted line in Fig. 3.…”
Section: Aggregation At the Toluene-water Interfacementioning
confidence: 99%
“…Molecular dynamics simulation studies confirmed that asphaltene aggregation results in the formation of complex structures both in the bulk and at the oil-water interface. [43][44][45][46] The strong selfaggregation of asphaltenes facilitates the adsorption of asphaltenes at oil-water interfaces, which is crucial for the stabilization of oil-water petroleum emulsions, and also the adsorption of asphaltenes onto mineral and metallic surfaces, which leads to plugging and fouling through entire oil production chains. 38 Copyright 2010 American Chemical Society.…”
Section: Asphaltenesmentioning
confidence: 99%
“…Recently, studies of prevention methods of asphaltene precipitation are attended very much [18]. Vanishing-Interfacial-Tension (VIT) is a new method, which could be used for understanding the asphaltene precipitation onset point [19][20][21][22][23]. This accurate method needs a small amount of sample for laboratory experiments [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…In this method, IFT would drastically increase after the onset point [27,28]. Precipitation mechanism, its rate, and onset point could be determined by analyzing the slope changes in the graph of IFT versus pressure [29,[21][22][23][24][25]. In addition, the VIT method gives information about the drop volume either at a specific pressure and temperature or during their increasing.…”
Section: Introductionmentioning
confidence: 99%